Fate of Sc-Ion Interaction With Water: A Computational Study to Address Splitting Water Versus Solvating Sc Ion - Kumar, Nandan; Kumar, Y. Bhargav; Sarma, Himakshi; Sastry, G. Narahari (Frontiers in Chemistry, 2021)
An exhaustive study of Sc-ion interaction with water molecules in all its possible oxidation and spin states has been carried out to delineate the relative propensity of Sc ions toward solvation and water splitting. Potential energy surface analysis of the Sc-ion reaction with water molecules, topological analysis of bonds, and the effect of sequential solvation up to 6 water molecules have been examined. Calculated values showed good agreement with the available experimental results. Close-shell systems such as singlet mono- and tricationic Sc ions prefer to split the water molecules. In contrast, the open-shell systems such as triplet mono- and doublet dicationic Sc ions prefer to get solvated than split the water molecule. Topological analysis of electron density predicted the Sc+/2+–water bond as a noncovalent bond while Sc3+–OH2, Sc2+–OH, and Sc+–H bonds as partially covalent in nature. Energy decomposition analysis revealed that Sc ion–water interactions are driven by electrostatic energy followed by polarization energy. The current study reveals that transition metal catalysis can be one of the most effective tools to employ in water splitting, by properly tuning the electrons, spin, and ligands around the catalytic center.